Açai seed biochar improves soil quality and black pepper seedling development in the Amazon region - Mendonça, Moises de Souza; Melo, Wanderley José de [UNESP]; Melo, Gabriel Maurício Peruca de; Bertipaglia, Liandra Maria Abaker; Araujo, Ademir Sergio Ferreira; Reis, Iolanda Maria Soares; Rocha, Sandra Mara Barbosa; Nogueira, Thiago Assis Rodrigues [UNESP]; Abreu-Junior, Cassio Hamilton; Jani, Arun Dilipkumar (Elsevier, 2024)
Sustainable management of the Amazon rainforest is fundamental for supporting life on earth because of its crucial role in sequestering carbon. One of the species grown in the forest is açaí (Euterpe oleracea), which is an important food and income source for its inhabitant. The acai seed, resulting from the processing of the fruit, is a solid organic residue, which has been an agent of undesirable environmental impacts such as natural landscape modifications, clogging sewers and water courses, eutrophication of surface waters. In this research, we evaluated the use of wood chips as a source of energy in a rustic oven to produce acai biochar so that family farmers carry out sustainable management of the residue and use biochar to improve soil quality and produce seedlings of native plants to regenerate degraded forests. The experiment was conducted in Pará, Brazil, Amazon region, using a randomized complete block design. A factorial treatment structure was implemented consisting of four biochar particle sizes (3, 5, 7, and 12 mm), 4 application rates (4, 8, 16, and 32 t ha−1), and a biochar-free control, with 5 replications. The results showed that the methodology for biochar production was easy to apply and low cost, allowing its use by family farmers. The combination of biochar rate and particle size affected soil properties and the development of black pepper seedlings in different ways. The soil properties affected were water retention capacity, moisture, fluorescein diacetate hydrolysis and arylsulphatase activity. The growth parameters of the affected black pepper seedlings were height and root system development.
Keywords: Amazon rainforest; Circular economy; Family farming; Organic waste; Rustic oven; Soil enzymes